Clinical outcomes of salvage radiotherapy in patients with supraclavicular lymph node metastases after esophagectomy - Ping, Zhang; Chanjun, Zhen; Wenwen, Bai; Mingyue, Chen; Quanbing, Su; Yajing, Wang; Zhiguo, Zhou (Frontiers in Oncology, 2023)
Purpose To evaluate the clinical outcomes of salvage radiotherapy in patients with supraclavicular lymph node (SCLN) metastases after esophagectomy. Methods After initial esophagectomy (R0 resection), clinical outcomes in patients with esophageal squamous cell carcinoma with SCLN metastases during follow-up were retrospectively analyzed. Results A total of 114 patients were split into two groups: the salvage radiotherapy (SR) (n=89) and the control (NSR) (without salvage radiotherapy, n=25). The overall survival rates of 1 year, 3 years and 5 years were 81.6%, 31.4% and 8.6%, accordingly. The 1-year and 3-year survival after SCLN metastases (SASM) rates were 40.2% and 14.5%, respectively; the median SASM time was 10 months. In the SR group, the SASM rates of 1-year and 3-year were 48.1% and 18.9%, compared to 12.0% and 0% in the NSR group (p<0.001). Patients in the SR group who received combined radiochemotherapy experienced 1-year and 3-year SASM rates of 62.6% and 33.4%, compared to 41.9% and 16.5% with single radiotherapy (p<0.001). The salvage radiation dose revealed that the 1-year and 3-year SASM rates turned out to be 56.5% and 23.4% in group of ≥60 Gy, and 29.2% and 7.5% in group of <60 Gy (p<0.001). According to multivariate analysis, combined visceral metastases (CVM), combined mediastinal failure (CMF), salvage radiotherapy, salvage radiation dose and salvage treatment method possibly were identified as important prognostic variables. After propensity score matching (PSM), the above results were similar to those before PSM, except for that only salvage radiotherapy is possibly independent prognostic variables for survival after SCLN metastases in multivariate analysis. Conclusion It is possible that salvage radiotherapy can increase the survival rate of patients who receive SCLN metastases following esophagectomy.